Antioxidant Activity of Ethanol and n-hexane Extracts of Javanese Bark (Lannea coromandelica) Using the DPPH Method - Taufiq, Nuramaniyah; Sulfiani, Sulfiani (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2023)
Javanese bark (Lannea coromandelica) contains secondary metabolites of saponins, tannins, phenolics, and flavonoids. Flavonoids include aromatic compounds that are antioxidants. Antioxidants can inhibit the oxidation process that arises due to free radical reactions to form unreactive compounds. The active flavonoid compounds in counteracting free radicals are determined by the presence of the –OH (hydroxy) functional group. Flavonoid compounds that have antioxidant properties include catechins, flavones, flavanones, flavonols, chalcones, and isoflavones. This study aims to determine the antioxidant activity of ethanol extract and n-hexane bark of Javan bark (Lannea coromandelica) using the DPPH method. The method used is DPPH using UV-VIS spectrophotometry. Ethanol extract has an IC50 of 3.996 mg/L and has a strong antioxidant activity while the antioxidant activity of N-Hexan is obtained IC50 2193.043 mg/L. has weak antioxidants weak antioxidants.